Report of Falcon Flight 19 April 2010 - Schumann, Ulrich; Schlager, Hans; Weinzierl, Bernadett; Reitebuch, Oliver; Minikin, Andreas; Huntrieser, Heidi; Sailer, Thomas; Mannstein, Hermann (Monitoring Volcanic Ash from Space, 2010)
This report presents the technical results, including lessons learned and recommendations, of the ESA-EUMETSAT workshop on Volcanic Ash Monitoring, which took place on 26 – 27 May 2010 at ESA/ESRIN in Frascati (Italy). 53 invited scientists from Universities, Meteorological Offices, Research Laboratories, national and international Agencies (e.g. DLR, EC, ECMWF, NASA, USGS) from Europe and the United States participated. Appenidx: A successful Falcon measurement flight was performed on 19 April 2010 for probing plumes over Germany from the Iceland Eyjafjoll volcano eruption. Layers of volcanic ash were detected by Lidar and probed in-situ with aerosol instruments. Under suitable viewing conditions, the ash layer was visible as a brownish layer to the observer. The horizontal and vertical distributions of the volcano layers were variable. In the plume layers particles larger than 3μm were detected at concentrations, not present in the free troposphere during unpolluted conditions. The concentrations of large particles measured in the volcano layers are comparable to concentrations measured typically in Saharan dust plumes but smaller compared to particle concentrations in the polluted boundary layer. An estimation of the particle mass concentration in the volcanic ash plume probed as part of a vertical profile over Leipzig at about 4 km altitude yield 60 μg/m3. After the flight the Falcon was inspected. So far no damages were observed including engines (after boroscopy) and windows. Further engine inspection is ongoing. Silver foils attached to under-wing stations showed no visible impact from volcanic ash.